BLOOD GROUP AND ITS RELATIONSHIP WITH DIABETIC - Hashim, Aswan Mahmood; Manje, Nawras Bahaa (PT. Antis International Publisher, 2025)
Objective: Diabetes is described in this article as a metabolic disease that results in hyperglycemia, or elevated blood sugar. DM pathophysiology may be divided into two primary groups. type 1 and type 2 Its connection to blood types is examined. The four basic